A Novel Scale Linking Potency and Dosage to Estimate Anticholinergic Exposure in Older Adults: the Muscarinic Acetylcholinergic Receptor ANTagonist Exposure Scale. Issue 6 (16th January 2017) - Klamer, Therese T.; Wauters, Maarten; Azermai, Majda; Durán, Carlos; Christiaens, Thierry; Elseviers, Monique; Vander Stichele, Robert
Abstract: Quantification of the anticholinergic exposure insufficiently or imprecisely incorporates dosage information, leading to inaccurate estimations. The aim was to construct a novel scale, including potency and dosage for the quantification of the anticholinergic exposure in older adults. Potency information was retrieved from a previous systematic review. The dosage range for each drug was delineated in minimal, maintenance and maximal dosage for adults and older adults. Dosage information was collected from authoritative sources and reviewed in an expert panel. The Muscarinic Acetylcholinergic Receptor ANTagonist Exposure (MARANTE) scale was tested for clinimetric properties using cohorts of community‐dwelling older adults and nursing home residents. After three data collection rounds, data for the dosage ranges remained incomplete for 32 active substances. Remaining gaps were filled in, and 11 dosage adjustments were proposed during the expert panel meeting. We chose the values 0; 1; 2) for the categories of potency and 0; 0.5; 1; 1.5; 2) for the levels of dosage ranges, showing good clinimetric properties. Forty‐one anticholinergic drugs were prescribed in the two cohorts. Most (61%) were low potency anticholinergics and used for depression (19%, e.g. citalopram). There were 31.8% (median MARANTE 1.5, IQR 1.5–2.5) and 37.6% (median 2, IQR 1.5–2.5) anticholinergic users in the community‐dwelling cohort and nursing home cohort, respectively. The MARANTE scale combines potency with the dosage spectrum, to quantify the anticholinergic exposure in older adults. An open feedback system on the list of anticholinergic and proposed anticholinergic potency and dosage values is advised.,